PENERAPAN PARTICIPATORY ERGONOMICS DALAM PERBAIKAN SISTEM K3 DI BAGIAN LAMINATING DAN CUTTING (STUDI KASUS DI PT PRIMARINDO ASIA INFRASTRUCTURE TBK) - Paulus Sukapto; Harjoto Djojosubroto; Kadek Audiandra (Badan Penerbit Jurnal, Faculty of Engineering, Universitas Brawijaya, 2016)
This research concerns with the applications of participatory ergonomics (PE) for workplace improvement in the laminating and cutting department of a shoe industry, PT Primarindo Asia Infrastructure TBK. PE refers to making employees, managers, ergonomists, health and safety personnel and research experts take part in the system design progresses early and completelly to increase their autonomy and direct influence on all aspects of the work that they are going to perform. The implementation of PE consists of the following steps: (1) the analysis of workplace conditions based on International Labour Organization’s safety standard checklist (2) hazard identification using Job Safety Analysis (3) risk score determination and (4) recommendation on what to be improved. In this respect we recommend to provide personal protective equipment for the employees, safety division also to improve the workplace safety.